Hydrothermal treatment of banana leaves for solid fuel combustion. Issue 9 (21st October 2021) - Mosqueda, Alexander; Medrano, Katleya; Gonzales, Hazel; Takahashi, Fumitake; Yoshikawa, Kunio
Abstract: Banana residues remain untapped for substantial thermochemical energy conversion. In this study, lab-scale production of hydrochar from banana leaves (BL) by hydrothermal treatment (HT) for solid fuel combustion was investigated. The HT was conducted at 180, 200 and 220 °C for 30 min, resulting in an energy yield of up to 94.0%. The fuel properties of BL were enhanced after HT. The carbon content increased with increasing reaction temperature while oxygen and ash content decreased. The higher heating values of the hydrochars (20.4–22.7 MJ/kg) were greater than that of its biomass origin. Changes in the structural and fuel properties influenced the combustion behavior and reactivity of hydrochars according to thermogravimetric analysis. A first-order reaction mechanism by Coats–Redfern approximation was adopted to describe the kinetics of non-isothermal combustion. This study may prove useful in evaluating the potential of hydrochar from banana leaves for solid fuel applications.